2022
DOI: 10.1002/jhbp.1274
|View full text |Cite
|
Sign up to set email alerts
|

Sequential histologic evolution of gallbladder inflammation in acute cholecystitis over the first 10 days after onset of symptoms

Abstract: Background The timing of cholecystectomy during acute cholecystitis (AC) is controversial, especially whether it is advisable to perform in patients with duration of symptoms between 3 and 10 days. The purpose of this study is to define clearly the sequential evolution of histological changes following symptoms onset to guide recommendations regarding timing of cholecystectomy. Methods We identified patients with AC (2005–2018) who had cholecystectomy within 10 days of symptom onset of a first attack of AC. Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…8 Regional inflammation in acute cholecystitis is relatively common. [9][10][11][12][13][14][15] Prior reporting has suggested that in a non-negligible number of cases, regional inflammation may be a triggering factor for acute cholecystitis. 11…”
mentioning
confidence: 99%
“…8 Regional inflammation in acute cholecystitis is relatively common. [9][10][11][12][13][14][15] Prior reporting has suggested that in a non-negligible number of cases, regional inflammation may be a triggering factor for acute cholecystitis. 11…”
mentioning
confidence: 99%